2005
DOI: 10.1016/j.orthres.2005.03.021.1100230606
|View full text |Cite
|
Sign up to set email alerts
|

Biological and mechanical changes of the bone graft–cement interface after impaction allografting

Abstract: In impaction allografting, the host bone interface may consist of morsellized allograft alone or as a composite with bone cement. The objective of this study was to investigate the temporal changes in the interface for these two materials in a rat bone chamber model. To simulate the impaired endosteal circulation after impaction allografting, bone chambers were tightened bilaterally to the endosteal surfaces of proximal tibiae of mature rats and filled with pure allograft or cement/allograft composite. The cem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Other mechanisms such as cement fatigue, 5 graft incorporation/fibrous invasion, 31,32 and cancellization of the femoral canal 33 are also suspected to play a role in implant stability, while previous studies also point to the importance of cement contact with the endosteum. 34,35 Nonetheless, clinical studies have shown that a substantial amount of subsidence develops in the early postoperative days: more than 1 mm subsidence was often observed within the first 3 months after surgery 36,37 and more than half of the subsidence observed at 6 weeks was seen typically within the first 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms such as cement fatigue, 5 graft incorporation/fibrous invasion, 31,32 and cancellization of the femoral canal 33 are also suspected to play a role in implant stability, while previous studies also point to the importance of cement contact with the endosteum. 34,35 Nonetheless, clinical studies have shown that a substantial amount of subsidence develops in the early postoperative days: more than 1 mm subsidence was often observed within the first 3 months after surgery 36,37 and more than half of the subsidence observed at 6 weeks was seen typically within the first 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, Piert et al 17 used Dynamic [18F] fluoride ion positron emission tomography (PET) to investigate the metabolic activity of allograft and concluded that the metabolic level was increased initially after surgery but decreased over time indicating allograft resorption. An animal study by Frei et al 18 also showed significant allograft resorption at 6 weeks, resulting in medullary canal widening and an unstable implant.…”
mentioning
confidence: 98%
“…8 ). Reduced movement within the impacted bone graft distal (Table 2 ) might be related to different distribution of energy during femoral impaction grafting (Fosse et al 2006a ; Frei et al 2005a , 2005b ). For particles being more prone to viscoplastic behavior than native bone like processed thermodisinfected bone the impaction force seems more important for the impaction than the particle size (Albert et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cement intrusion in the distal two thirds of impacted bone graft seemed mainly determined by graft permeability and appeared reduced distal in thermodisinfected compared with native cancellous bone (Fölsch et al 2018 ; Frei et al 2004 , 2006 ) which might reflect reduced porosity of impacted thermodisinfected cancellous bone in the distal region (Fig. 8 ) (Frei et al 2005b ) since increased air in the proximal region of thermodisinfected cancellous bone was shown (Fölsch et al 2018 ). This could be related to differences of micromovement at the proximal and distal point of measurement in the thermodisinfected bone specimens compared with native bone (Ohashi et al 2009 ) (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation